Golden gulag : prisons, surplus, crisis, and opposition in globalizing California - Gilmore, Ruth Wilson, 1950- (American crossroads, 2007)
Since 1980, the number of people in U.S. prisons has increased more than 450%. Despite a crime rate that has been falling steadily for decades, California has led the way in this explosion, with what a state analyst called "the biggest prison building project in the history of the world." Golden Gulag provides the first detailed explanation for that buildup by looking at how political and economic forces, ranging from global to local, conjoined to produce the prison boom.